Pemanfaatan Model Project Based Learning dalam Meningkatkan Kemampuan Bersastra dan Berdrama Mahasiswa - Fransori, Arinah; Parwis, Friza Youlinda (Jurnal Pendidikan Impola, 2025)
This study aims to analyze the effectiveness of the Project-Based Learning (PjBL) model in improving students' literary and drama skills in the language and literature education study program. The underlying problem is low student participation and suboptimal dramatic appreciation and expression skills in lecture-centered learning. This study uses a qualitative descriptive approach that describes the project and the steps in the literary and drama process. The subjects were 40 fifth-semester students. Data were collected through literary ability tests, drama performance assessments, and observation sheets for learning activities. The results show that the implementation of the PjBL model significantly improved students' literary analysis skills, scriptwriting creativity, and role-playing skills compared to conventional learning. Therefore, the PjBL model is effective as an innovative learning alternative in literature and drama courses at universities.